Predictors of Sudden Cardiac Death during Extracardiac Surgical Interventions - L. A. Maltseva; N. V. Krasnenko; V. V. Khalimonchik; R. A. Shkapyak (Общая реаниматология)
The paper presents the currently available data in the literature on sudden cardiac death (SCD), including its definition, epidemiology, etiology, risk factors, predisposition to the development of SCD, the ways of assessing the risk of SCD. It outlines myocardial morphological changes in the development of SCD, the pathogenesis of the major links of the origin of ventricular fibrillation in myocardial ischemia, and the mechanisms responsible for the development of SCD. A relationship has been established between coronary heart disease and the risk of developing SCD. Particular attention is given to the topicality of the problem of SCD to inpatients: at the stages of anesthetic management during extracardiac surgical interventions. Emphasis is placed on the importance of preoperative meticulous examination of the patients. A number of the drugs that are most frequently used in anesthesiology and negative affect the myocardium and systemic hemodynamics are listed, which is extremely important to patients having initially cardiovascular diseases. The detection of the predictors of SCD in the preop-erative period and the methods of studying the patients, among which scale, instrumental, and biochemical methods being emphasized, feature in the paper. Recommendations to improve the quality of perioperative management and to increase the safety of anesthetic maintenance are listed.